Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's solve the problem step-by-step.
We are given a polynomial [tex]\( f(x) = x^3 - 5x^2 + 7x - 15 \)[/tex] and asked to find the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex], where [tex]\(\alpha, \beta, \gamma\)[/tex] are the roots of the polynomial.
First, let's recall Vieta's formulas, which relate the coefficients of the polynomial to sums and products of its roots. For a cubic polynomial of the form [tex]\( f(x) = x^3 + ax^2 + bx + c \)[/tex], the relationships are:
1. [tex]\(\alpha + \beta + \gamma = -\frac{\text{coefficient of } x^2}{\text{leading coefficient}}\)[/tex]
2. [tex]\(\alpha\beta + \beta\gamma + \gamma\alpha = \frac{\text{coefficient of } x}{\text{leading coefficient}}\)[/tex]
3. [tex]\(\alpha\beta\gamma = -\frac{\text{constant term}}{\text{leading coefficient}}\)[/tex]
For our polynomial [tex]\( f(x) = x^3 - 5x^2 + 7x - 15 \)[/tex], the leading coefficient (coefficient of [tex]\( x^3 \)[/tex]) is 1.
According to Vieta's formulas:
1. [tex]\(\alpha + \beta + \gamma = -\left(-5\right) = 5\)[/tex]
2. [tex]\(\alpha\beta + \beta\gamma + \gamma\alpha = 7\)[/tex]
3. [tex]\(\alpha\beta\gamma = -(-15) = 15\)[/tex]
We need to find the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex].
Notice that:
[tex]\[ (\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1} = \frac{1}{\alpha \beta} + \frac{1}{\beta \gamma} + \frac{1}{\gamma \alpha} \][/tex]
To simplify these fractions, we find a common denominator, which is:
[tex]\[ \alpha \beta \cdot \beta \gamma \cdot \gamma \alpha = (\alpha \beta \gamma)^2 \][/tex]
Now, we rewrite the expression:
[tex]\[ \frac{1}{\alpha \beta} + \frac{1}{\beta \gamma} + \frac{1}{\gamma \alpha} = \frac{\gamma \alpha \beta + \alpha \beta \gamma + \beta \gamma \alpha}{(\alpha \beta \gamma)^2} \][/tex]
Since addition in the numerator is simply the sum of all product pairs of roots, because of symmetry:
[tex]\[ = \frac{3\alpha \beta \gamma}{(\alpha \beta \gamma)^2} = \frac{3 \alpha \beta \gamma}{(\alpha \beta \gamma)^2} \][/tex]
We know from Vieta's formulas that:
[tex]\[ \alpha \beta \gamma = 15 \][/tex]
Substitute this into the expression:
[tex]\[ = \frac{3 \times 15}{(15)^2} = \frac{45}{225} = \frac{1}{5} \][/tex]
Therefore, the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex] is:
[tex]\[ \boxed{\frac{1}{5}} \][/tex]
We are given a polynomial [tex]\( f(x) = x^3 - 5x^2 + 7x - 15 \)[/tex] and asked to find the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex], where [tex]\(\alpha, \beta, \gamma\)[/tex] are the roots of the polynomial.
First, let's recall Vieta's formulas, which relate the coefficients of the polynomial to sums and products of its roots. For a cubic polynomial of the form [tex]\( f(x) = x^3 + ax^2 + bx + c \)[/tex], the relationships are:
1. [tex]\(\alpha + \beta + \gamma = -\frac{\text{coefficient of } x^2}{\text{leading coefficient}}\)[/tex]
2. [tex]\(\alpha\beta + \beta\gamma + \gamma\alpha = \frac{\text{coefficient of } x}{\text{leading coefficient}}\)[/tex]
3. [tex]\(\alpha\beta\gamma = -\frac{\text{constant term}}{\text{leading coefficient}}\)[/tex]
For our polynomial [tex]\( f(x) = x^3 - 5x^2 + 7x - 15 \)[/tex], the leading coefficient (coefficient of [tex]\( x^3 \)[/tex]) is 1.
According to Vieta's formulas:
1. [tex]\(\alpha + \beta + \gamma = -\left(-5\right) = 5\)[/tex]
2. [tex]\(\alpha\beta + \beta\gamma + \gamma\alpha = 7\)[/tex]
3. [tex]\(\alpha\beta\gamma = -(-15) = 15\)[/tex]
We need to find the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex].
Notice that:
[tex]\[ (\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1} = \frac{1}{\alpha \beta} + \frac{1}{\beta \gamma} + \frac{1}{\gamma \alpha} \][/tex]
To simplify these fractions, we find a common denominator, which is:
[tex]\[ \alpha \beta \cdot \beta \gamma \cdot \gamma \alpha = (\alpha \beta \gamma)^2 \][/tex]
Now, we rewrite the expression:
[tex]\[ \frac{1}{\alpha \beta} + \frac{1}{\beta \gamma} + \frac{1}{\gamma \alpha} = \frac{\gamma \alpha \beta + \alpha \beta \gamma + \beta \gamma \alpha}{(\alpha \beta \gamma)^2} \][/tex]
Since addition in the numerator is simply the sum of all product pairs of roots, because of symmetry:
[tex]\[ = \frac{3\alpha \beta \gamma}{(\alpha \beta \gamma)^2} = \frac{3 \alpha \beta \gamma}{(\alpha \beta \gamma)^2} \][/tex]
We know from Vieta's formulas that:
[tex]\[ \alpha \beta \gamma = 15 \][/tex]
Substitute this into the expression:
[tex]\[ = \frac{3 \times 15}{(15)^2} = \frac{45}{225} = \frac{1}{5} \][/tex]
Therefore, the value of [tex]\((\alpha \beta)^{-1} + (\beta \gamma)^{-1} + (\gamma \alpha)^{-1}\)[/tex] is:
[tex]\[ \boxed{\frac{1}{5}} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.